RESEARCH STATUS AND DEVELOPMENT OF MICRO/NANO TEXTURE - LI Dan; YANG XueFeng; WANG ShouRen; LIU WenBo; WAN Zhuang; XIA GuoFeng (Jixie qiangdu)
Machining the micro/nano texture on the surface of the workpiece can effectively improve the surface bearing capacity of the friction pair,while reducing the friction coefficient,friction and wear.Through the research and development status of micro/nano texture,the key design parameters,processing methods,friction reduction mechanism and micro/nano texture combined with coating technology are comprehensively expounded.Among them,the shape,depth,aspect ratio and area ratio of the texture are important parameters which have an impact on the friction and wear; pulsed laser processing technology has the most development prospect in micro/nano texture processing technology;according to the different anti-friction mechanisms of texture under different lubrication conditions,it can be applied to many fields such as machining,biomedicine,etc;the combination of micro/nano texture and coating can improve the bonding force between the coating and the tool surface,thereby improving the cutting performance and anti-bonding wear performance of the tool.Finally,the problems and research prospects in the study of the texture of the friction pair surface and its influence on the tribological properties are pointed out.